1981
DOI: 10.1063/1.441082
|View full text |Cite
|
Sign up to set email alerts
|

Single and double ionization of nitric oxide by electron impact from threshold up to 180 eV

Abstract: Electron impact ionization of nitric oxide was studied as a function of electron energy up to 180 eV. A double focusing mass spectrometer in combination with an improved electron impact ion source (Stephan et al.) was used, alleviating the problems of ion extraction from the source and the transmission of the extracted ions through the mass spectrometer system. Relative partial ionization cross section functions were measured for the processes NO+e→NO++2e and NO+e→NO2++3e. An accurate determination of the cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 42 publications
7
23
0
Order By: Relevance
“…The ''kink'' near Tϭ20 eV is the artifact of the BEB model because the model cannot account for autoionizing states between the lowest B and Tϳ20 eV that must have been included in the experimental cross sections. Indeed, the experimental data by Kim et al 28 ͑not shown in the figure͒ agree very well with those by Rapp and Englander-Golden for Tр40 eV, indicating that the experimental data by Iga et al at 10ϽTϽ30 eV are too low.…”
Section: A Diatomic Moleculessupporting
confidence: 75%
“…The ''kink'' near Tϭ20 eV is the artifact of the BEB model because the model cannot account for autoionizing states between the lowest B and Tϳ20 eV that must have been included in the experimental cross sections. Indeed, the experimental data by Kim et al 28 ͑not shown in the figure͒ agree very well with those by Rapp and Englander-Golden for Tр40 eV, indicating that the experimental data by Iga et al at 10ϽTϽ30 eV are too low.…”
Section: A Diatomic Moleculessupporting
confidence: 75%
“…The present NO ϩ cross section is shown in Fig. 5͑a͒ together with those of Kim et al 15 and of Iga, Rao, and Srivastava 2 for which the experimental uncertainties are given as Ϯ20% and Ϯ15%, respectively. The results of Kim et al 15 agree with the present measurements within the combined uncertainties, but above 100 eV the energy dependence of the two measurements differs somewhat.…”
Section: Results and Discussion: Nomentioning
confidence: 90%
“…5͑a͒ together with those of Kim et al 15 and of Iga, Rao, and Srivastava 2 for which the experimental uncertainties are given as Ϯ20% and Ϯ15%, respectively. The results of Kim et al 15 agree with the present measurements within the combined uncertainties, but above 100 eV the energy dependence of the two measurements differs somewhat. The results of Iga, Rao, and Srivastava 2 lie much higher than the present data and the sharp decrease in the cross section observed by these workers below 40 eV is not in accord with the present measurements, or with those of Kim et al 15 The only previous measurement of the individual N ϩ and O ϩ partial cross sections appears to be that of Iga, Rao, and Srivastava 2 ͓Figs.…”
Section: Results and Discussion: Nomentioning
confidence: 94%
See 1 more Smart Citation
“…This radical, possibly created at the hot filament from residual N 2 and O 2 , has an ionization potential around 10 eV. 43 The presence of contamination together with a relatively low density in front of the mass spectrometer are probably also the reasons why SiH and Si radicals could not be detected. The low radical densities can be due to a small production rate or to a large loss rate, e.g., by fast reactions with SiH 4 as will be addressed in Sec.…”
Section: ϫ13mentioning
confidence: 99%